Comparison of Synchronization Indices: Behavioral Study. (16th April 2009) - Dugué, Pierre; Bouquin-Jeannès, Régine Le; Faucon, Gérard
Abstract : The synchronization of a neuronal response to a given periodic stimulus is usually measured by Goldberg and Brown's vector strength metric. This index does not take omitted spikes into account. This particular limitation has motivated the development of two new indices: the corrected vector strength index and the corrected phase variance index, both including a penalty factor linked to the firing rate. In this paper, a theoretical study on the normalization of the corrected phase variance index is conducted. Both indices are compared to four existing ones using a simulated dataset which considers three desynchronizing disturbances: irregularity in firing, added spikes, and omitted spikes. In the case of unimodal responses, the two new indices are satisfying and appear the more promising in the case of real signals. In the multimodal case, the entropy-based index is better than the others even if this index is not drawback-free.